Development of E-Modules Based on the Socrates Method to Improve Learning Outcomes of Madrasah Ibtidaiyah Students in Mathematics Subjects - Anggili Pratama; Eva Faridah; Nurdin Bukit; Edy Surya (Institut Agama Islam Negeri Palopo, 2023)
This research aims to developÂ e-module based on the Socratic method. This research is research and development. This research uses the ADDIE development model, including analyze, design, develop, implement, and evaluate. This research only reached the implementation stage. The research was carried out inMIS AL Hidayah Sidomulyo.The research subjects were 20 class V students, consisting of 9 male students and 11 female students. The research object is an e-module based on the Socratic method to improve student learning outcomes. Data collection techniques are observation, tests and questionnaires. The data analysis techniques used are: (a) e-module analysis based on the Socratic method; (b) the effectiveness of e-modules based on the Socratic method. Based on validation results by media experts with a percentage of 94.85%, it is categorized as very feasible. The results of validation by material with a percentage of 94.65% are categorized as very feasible. Meanwhile, validation results by language with a percentage of 89.75% are categorized as very feasible. The results of the pretest trial were with a percentage of 45% with 3 students who completed it and 17 students who did not complete it. Meanwhile, the posttest trial had a percentage of 83.5% with 19 students who completed and 1 student who did not complete.It can be concluded that the e-module based on the Socratic method is feasible and effective to use.